Making the most of the old age: Autumn breeding as an extra reproductive investment in older seabirds. Issue 10 (26th March 2021) - Ramírez, Francisco; Chiaradia, Andre; O'Leary, Danielle A.; Reina, Richard D.
Abstract: The extrinsic and intrinsic factors affecting differing reproductive strategies among populations are central to understanding population and evolutionary ecology. To evaluate whether individual reproductive strategies responded to annual patterns in marine productivity and age‐related processes in a seabird we used a long term (2003–2013), a continuous dataset on nest occupancy and attendance at the colony by little penguins ( Eudyptula minor ) at Phillip Island (Victoria, Australia). We found that concurrent with a secondary annual peak of marine productivity, a secondary peak in colony attendance and nest occupancy was observed in Autumn (out of the regular breeding season in spring/summer) with individuals showing mating‐like behavior. Individuals attending this autumn peak averaged 2.5 years older than those individuals that exclusively bred during spring/summer. Rather than being a naïve response by younger and inexperienced birds misreading environmental cues, our data indicate that the autumn peak attendance is an earlier attempt to breed by older and more experienced penguins. Therefore, we provide strong support for the fundamental prediction of the life‐history theory of increasing investment in reproduction with age to maximize lifetime fitness as future survival prospects diminish and experience increases. Abstract : We use an eleven‐year dataset of bird breeding to test the life‐history theory that predicts a relationship between reproductive investment and age. We examined the pattern of attendance at the colony and demographic information of little penguins to detect a peak in breeding activity during autumn, in addition to the usual breeding peak in spring/summer. We found that there was a significant difference in age of birds that bred in one or both these peaks, indicating an increased investment by older birds in accordance with theory predicting their diminished future reproductive potential and capacity to accurately detect environmental cues.